Progressive multifocal leukoencephalopathy after durvalumab treatment for acute myeloid leukemia: A consequence of an immune reconstitution inflammatory syndrome?. Issue 3 (29th May 2022) - Vinatier, Emeline; Poli, Caroline; Giltat, Aurélien; Nunes‐Gomes, Christopher; Orvain, Corentin; Hunault‐Berger, Mathilde; Jeannin, Pascale; Thépot, Sylvain
Abstract: Progressive multifocal leukoencephalopathy (PML) is a fatal demyelinating disease of the central nervous system resulting from the reactivation of the John Cunningham virus (JCV). PML occurs almost exclusively during profound immune suppression but it can also be observed in immunocompromised subjects as part of an inflammatory immune reconstitution syndrome (IRIS) in patients receiving antiviral therapy. We report a case of PML in a 61‐year‐old patient with acute myeloid leukemia who had developed after discontinuation of durvalumab (anti‐PD‐L1) therapy initiated after multiple treatments. Results suggest that PML may result from two nonexclusive mechanisms: (i) an inhibition of the protective response of JCV‐specific T cells as a consequence of the blockade of the PD1‐PDL1 pathway, associated with a lack of compensatory expression of other inhibitory receptors by T cells and (ii) a neuroinflammatory response (PML‐IRIS) that may have contributed to virus reactivation.